Student Lifestyle and Social Pressure in Educational Environment - Muhibatul Muyasyaroh; Adinda Sabrina Salsabila; Muhammad Syafiurrahman; Muhammad Ryja Baihaqi; Abdul Fadhil (Kawakib: Journal of Multidisciplinary Research, 2026)
The world of education today is not only a space for academic development but also a social arena where students' identity and existence are shaped. Along with the massive development of digital technology and social media, there has been a significant shift in student lifestyles that triggers the emergence of a consumerist culture, the "flexing" phenomenon, and the fear of missing out (FOMO). This article aims to examine the lifestyle of students and the forms of social pressure (peer pressure) that arise within the educational environment, along with their impacts on students' psychosocial development. The method used in this writing is a literature review sourced from books, scientific articles, and other relevant references. The results of the discussion indicate that the strong urge to conform to the standards of both digital and real social groups has shifted students' social interaction patterns from face-to-face to online communication. The combination of modern lifestyle demands and academic expectations from teachers, parents, and institutions potentially creates a double burden that triggers anxiety, low self-esteem, and a decline in students' mental health. Through this study, it is hoped that educators, parents, and students can reflect together to create a healthier, more adaptive, and supportive educational environment.